Effects of AlN/GaN superlattice buffer layer on performances of AlGaN/GaN HEMT grown on silicon for sub-6 GHz applications. (1st February 2023) - Hieu, Le Trung; Hsu, Heng-Tung; Chiang, Chung-Han; Panda, Debashis; Lee, Ching-Ting; Lin, Chun-Hsiung; Chang, Edward Yi
Abstract: In this study, the effects of AlN/GaN superlattice (SL) thickness on performances of AlGaN/GaN high electron mobility transistor (HEMT) heterostructure grown by metal-organic chemical vapor deposition on silicon is investigated. Stress in GaN is controlled by varying the total thickness of the AlN/GaN SL. Improved crystal quality and surface roughness accomplished with 2200 nm-thick AlN/GaN SL, leads to an increase in high electron mobility (1760 cm 2 (V s) −1 ) as well as two-dimensional electron gas concentration (1.04 × 10 13 cm −2 ). AlGaN/GaN metal–insulator-semiconductor HEMT (MIS-HEMT) fabricated on the heterostructure with SL buffer layer exhibits a significant improvement in maximum saturation current of 1100 ± 29 mA mm −1 at V GS = 0 V and a low on-resistance of 4.3 ± 0.15 Ω mm for the optimized AlN/GaN SL. The 2200 nm-thick AlN/GaN SL supports the growth of stress-free GaN heterostructure, which can reduce the insertion loss for sub-6 GHz radio frequency (RF) applications. This GaN HEMT structure based on SL buffer layer is suitable for low-frequency RF power applications.